Why is Asari (=Manila) clam Ruditapes philippinarum fitness poor in Arcachon Bay: A meta-analysis to answer?. (20th September 2016) - de Montaudouin, X.; Lucia, M.; Binias, C.; Lassudrie, M.; Baudrimont, M.; Legeay, A.; Raymond, N.; Jude-Lemeilleur, F.; Lambert, C.; Le Goïc, N.; Garabetian, F.; Gonzalez, P.; et al.
Abstract: Asari (=Manila) clam, Ruditapes philippinarum, is the second bivalve mollusc in terms of production in the world and, in many coastal areas, can beget important socio-economic issues. In Europe, this species was introduced after 1973. In Arcachon Bay, after a decade of aquaculture attempt, Asari clam rapidly constituted neo-naturalized population which is now fished. However, recent studies emphasized the decline of population and individual performances. In the framework of a national project (REPAMEP), some elements of fitness, stressors and responses in Arcachon Bay were measured and compared to international data (41 publications, 9 countries). The condition index (CI = flesh weight/shell weight) was the lowest among all compared sites. Variation in average Chl a concentration explained 30% of variation of CI among different areas. Among potential diseases, perkinsosis was particularly prevalent in Arcachon Bay, with high abundance, and Asari clams underwent Brown Muscle Disease, a pathology strictly restricted to this lagoon. Overall element contamination was relatively low, although arsenic, cobalt, nickel and chromium displayed higher values than in other ecosystems where Asari clam is exploited. Finally, total hemocyte count (THC) of Asari clam in Arcachon Bay, related to the immune system activity, exhibited values that were also under what is generally observed elsewhere. In conclusion, this study, with all reserves due to heterogeneity of available data, suggest that the particularly low fitness of Asari clam in Arcachon Bay is due to poor trophic condition, high prevalence and intensity of a disease (perkinsosis), moderate inorganic contamination, and poor efficiency of the immune system. Highlights: Asari clams characteristics are compared among 9 countries through 41 references. 30% of condition index variation is explained by chlorophyll a concentration. Chl a and diseases explain most of Asari clam poor fitness in Arcachon Bay.